Gene X-pert Positivity and its Relation with Tuberculin Skin Test (TST) in Tuberculosis Suspected Children Visiting Tertiary Care Pediatric Center of Nepa - Bhattarai, Tribhuwan; Chapagain, Ram Hari; Adhikari, Santosh; Basnet, Chandra Kiran; Subedi, Rasish; Basnet, Reiha Kiran; Thakali, Pramila (Journal of Karnali Academy of Health Sciences, 2025)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis, is among the top ten leading causes of death worldwide. Pulmonary TB is the most common form of TB and is easily transmitted through aerosol droplets. Gene- X-pert MTB/RIF can perform rapid detection of M. tuberculosis (MTB) and its resistance to rifampicin. Mantoux tuberculin skin test (TST) is used to determine whether a person is infected with M. tuberculosis by measuring the size of induration 72 hours after inoculation. The main objective of the study was to observe the relation of the mantoux test with Gene X-pert test for detection of tuberculosis.Method: We reviewed the data of the patients who underwent Gene X-pert testing in Kanti children’s Hospital (KCH) in the last two years. The Mantoux test and the Gene X-pert data were collected with sociodemographic data of children. The data were collected and the frequency tables were prepared and analyzed. The descriptive analysis was done using the frequency table.Results: Among 622 TB-suspected children, 46 (7.4%) were Gene X-pert positive. Mantoux TST results were available in 249 cases, with 87 (34.9%) testing positive (≥10 mm induration). Of these, only 12.6% (n=11) were also Gene X-pert positive. The Mantoux test showed a sensitivity of 44%, specificity of 66.1%, PPV of 12.6%, and NPV of 91.4% against Gene X-pert. Gene X-pert testing was more frequently performed in males (63.7%), but positivity was higher in females (58.7%). Mantoux positivity was slightly more common in males (59.8%) than females (40.2%). Most TB suspects and Gene X-pert positive cases were from Bagmati province (46.1% and 52.2%, respectively), followed by Madhesh. Brahmin/Chhetri and Janajati ethnic groups were the most represented among both TB suspects and confirmed cases.Conclusion: The Mantoux test showed low sensitivity (44%) and poor positive predictive value (12.6%) compared to Gene X-pert, limiting its role in pediatric TB diagnosis. It should not be used alone for screening or treatment decisions. Gene X-pert remains crucial for accurate confirmation of TB in children.